Intestinal obstruction in von Recklinghausen's disease. (October 2014) - Trilling, B.; Faucheron, J.‐L.
Abstract Aim Gastrointestinal manifestations occur in up to 25% of patients with neurofibromatosis type 1. This review reports all published cases of acute intestinal obstruction due to neurofibromatosis type 1 and identifies mechanisms of obstruction, the nature of the tumour and the outcome. Method A systematic review of the literature on acute intestinal obstruction due to neurofibromatosis type 1 was performed by searching the major electronic databases. All relevant references were reviewed for possible inclusion. All the references of the relevant articles were screened for any further articles that were missed in the initial search. Results We identified 25 articles from 1972 to 2013 reporting 25 patients with von Recklinghausen's disease who underwent laparotomy for acute intestinal obstruction. Three further patients were operated on in our institution. The mean age of the patients was 44.2 years and the male/female ratio 15/13. The mechanisms of obstruction were intrinsic obstruction (16), extrinsic obstruction (8) and intussusception (4). Histology was reported to show neurofibroma (19), gastrointestinal stromal tumour (5) and adenocarcinoma (4). Among patients whose outcome was mentioned (17), 10 were asymptomatic after a mean follow‐up of 1.5 years. Conclusion Acute bowel obstruction is a rare manifestation of neurofibromatosis type 1. Surgery is often necessary to treat the complication and to determine the exact nature of the tumour and the prognosis.